The Significance of Training in Organizations on the Performance and Capabilities of Employees (Global Journal of Management and Business Research, 2019)
Introduction-The objective of this paper is to discuss the significance of training in organizations on the performance and capabilities of employees. It is not doubted that presently, organizations across the world are doing what they can to achieve enhanced competitiveness and success in their respective industries. Success comes at a price and it is imperative that such organizations be capable of obtaining and utilizing their human resources in the most optimal and effective way possible. It is very important for organizations to have awareness of the apparent importance of the human resources. The management of these organizations must provide special attention to ensuring that all of the main human resource management functions are optimal and in line with the organizational objectives.
Keywords: human resource management practices; training and development; organizational performance; organizational commitment